A modified Wenzel model for water wetting on van der Waals layered materials with topographic surfaces. Issue 11 (2nd March 2017) - Zhao, Peng; Huang, Yongfeng; Shen, Yutian; Yang, Shuo; Chen, Lan; Wu, Kehui; Li, Hui; Meng, Sheng
Abstract : The modified Wenzel model provides a generalized wetting picture for vdW layered materials with terraced topographic surfaces. Abstract : A modified Wenzel model is proposed for describing the wetting behavior of van der Waals layered materials with topographic surfaces, based on the measured linear relationship between water wetting and surface roughness for high quality Bi2 Se3 thin films, synthesized using molecular beam epitaxy (MBE) in the optimized temperature window of 180–200 °C. The water contact angles are found to have apparent dependence on the nanoscale surface morphology, enabling film wettability as a new tool to quickly characterize the quality of atomically thin films. The water contact angle of the ideal Bi2 Se3 surface is inferred to be ∼98.4°, indicating its intrinsic hydrophobic nature; however, the edge of the terrace on its surface is extremely hydrophilic, leading to easy hydrophobic/hydrophilic transitions. The atomistic mechanism is further revealed by first principles calculations. The regulated wettability is of great importance for electronic applications of Bi2 Se3 and other two-dimensional materials with distinctive electronic structures.